MARK activation in human blood mononuclear cells in types 1 and 2 diabetes - Pushkarev, V.V.; Sokolova, L.K.; Kovzun, O.I.; Cherviakova, S.A.; Vatseba, T.S.; Pushkarev, V.M.; Tronko, M.D. (Reports of the National Academy of Sciences of Ukraine, 2020)
The peripheral blood mononuclear cells (PBMC) mainly includes monocytes and lymphocytes involved in the development of diabetes mellitus and other autoimmune diseases. Ret/Ras/Raf/MEK/ERK (mitogen-activated protein kinases, MAPK) is a signaling cascade that controls cellular processes such as proliferation, survival, angiogenesis, cell growth, and motility. The aim of the work was to study the activation in PBMC of the main effector protein kinase of this cascade — ЕRК1/2. Enzyme-linked immunosorbent assay kits were used to determine the amount of phospho-ЕRК1/2. It is shown that activation of ЕRК1/2 in PBMC of patients with type 2 diabetes is not observed, while it increased significantly in pa tients with type 1 diabetes or autoimmune thyroiditis. However, in patients with type 1 diabetes with autoimmune thyroiditis, the activation of ЕRК1/2 in PBMC decreases to a control level, which can be explained by the competition between the two autoimmune processes for common signaling pathways. The role of the MAPK cascade in the pathogenesis of autoimmune diseases is discussed.